MENAKAR KEKAFIRAN BERFIKIRTERHADAP KEBERADAAN PEREMPUAN DALAM SEJARAH PERADAMAN MANUSIA - Abubakar Muhammad Nur (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2017)
Before the coming of the islamic civilization, the existence of women is just as “spread” for the male voice and the cry of women compensation whenever it “My Body Seems By Not Mine”. Social theory position “Dignity” women and men have “Equality” in this role and function in various space, Islam position “Degrees” of men and women in accordance with his nature, the existence of “Balance” role and function in the the share of primary space. Hack back in disbelief thinking about the role and function of women, so as not to ceuse misunderstanding or misinterpretation of the presence of women in the male zone.